FAKTOR-FAKTOR YANG MEMPENGARUHI GREEN COMPETITIVE ADVANTAGE - Yulia Nur Atriksa Yulia Nur Atriksa; Etty Murwaningsari (Jurnal Riset Akuntansi, 2022)
This study aims to examine and analyze the effect of environmental organizational culture, environmental leadership, environmental capability, green innovation, green supply chain management, and green organizational culture on green competitive advantage. This study analyzes the influence between variables through hypothesis testing (causality research). The data used are secondary data from sustainability reports and/or annual reports of companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2021.There are 369 research samples that meet the predetermined criteria (purposive sampling method). Data analysis using SPSS version 22.0. The result is that environmental leadership, environmental capability, and green supply chain management have a significant positive effect on green competitive advantage, while environmental organizational culture, green innovation, and green organizational culture have no effect on green competitive advantage.